Indecomposable and isomorphic objects in the category of monomial matrices over a local ring - Bondarenko, V. M.; Bortos, M. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We study the indecomposability and isomorphism of objects from the category of monomial matrices $Mmat(K)$ over acommutative local principal ideal ring $K$ (whose objects are square monomial matrices and the morphisms from $X$ to $Y$ are the matrices $C$ such that $XC = CY$). We also study the subcategory $Mmat_0(K)$ of the category $Mmat(K)$ with thesame objects and only those morphisms that are monomial matrices.